(untitled) (Cadernos de Sociomuseologia, 2020)
The work aims to analyze the musealization process carried out by the Ecomuseu Ilha Grande. We highlight the relationship between theory and practice of an Ecomuseum, prioritizing the integrated performance of the communities that inhabit Ilha Grande and their involvement in the musealization of the territory and in the definition of its heritage. The theoretical-conceptual foundation involves the notions of territory, society, integral heritage, community participation, local development and the environment. The methodological procedure adopted focuses especially on the community of Vila Dois Rios, where the headquarters of the Ecomuseu Ilha Grande is located and uses the Experimental Laboratory proposal, understanding Vila and its community as a space for collective construction. Key words: Ecomuseu Ilha Grande; Musealization; Community; Heritage.